(3bUjOI GdHOjYIs - (3YR GdOjf CHh GdMSf Hf HgGA GdOjf GdMSjf GdehUdj GdMfHdis; (3ESeGYjd Hf Ydj Hf eMehO Hf eMeO Hf YeQ Hf TGgfTGg Hf CjhH(B: (3Gdedc GdeDjO, UGMH MeGI,J (B732 (3g` s ((3GdLGeY GdCehi s)
(3ChdgG (B:s
(3HOG ef GdHOh HOQ Je abdJ eG GdGSe bGd jMji GSeg hNdag GdfLH bdJ jgPi def JQGgG abGd jMji HNHi s
(3BNQgG (B:s
(3abdJ eGPG Cbhd deG COYhG Edgi abGd jMji HLfi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B16s
(3HgG fXGe GdJYbjHIs
(3HBNQg CHjGJ TYQjI CNQi ddeDdas
(3HBNQg ahGFO hGHjGJ TYQjI eNJdaIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs